Mechanical properties, springback, and formability of W-temper and peak aged 7075 aluminum alloy sheets: Experiments and modeling. (15th March 2020) - Choi, Yumi; Lee, Jinwoo; Panicker, Sudhy S.; Jin, Hong-Kyo; Panda, Sushanta Kumar; Lee, Myoung-Gyu
Highlights: Formability and springback in cold forming of peak-aged 7075 aluminum alloy sheets. Anisotropic hardening under loading path changes were modeled. Improved formability and lowered springback with heat-treated 7075 aluminum alloy sheets. The analysis on Formability prediction using MK model by considering serrated flow. Abstract: High strength aluminum alloys have drawn much attention as the requirement for lightweight vehicle design increases in the automotive industry. However, inferior formability due to higher strength poses a technical hurdle against successful application of high strength aluminum sheets in automotive components. In this study, the mechanical properties of 7075 aluminum alloy sheet after W-temper heat treatment, which consists of solution heat treatment and subsequent quenching, are investigated. Detailed experimental and numerical studies are conducted on the anisotropy, non-proportional deformation behavior, and corresponding constitutive modeling in comparison with the corresponding characteristics of peak aged T6 heat-treated as-received alloy sheets. Based on the experimentally characterized mechanical properties and associated constitutive laws, the formability and springback of the W-tempered sheet are analyzed using the Marciniak–Kuczyinski forming limit diagram and U-draw bending springback simulations, respectively, by employing the Yld2000-2d anisotropic yield function and distortional hardening-based homogeneous anisotropic hardening model. Additionally, the improved constitutive modeling of the W-tempered 7075 aluminum sheets due to the effect of serrated flow characteristics on the hardening and frictional behaviors is discussed. Graphical abstract: Image, graphical abstract